2016
DOI: 10.5539/ibr.v9n2p34
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Entrepreneurial Intention and Innovativeness of University Students: The Mediating Role of Entrepreneurial Alertness

Abstract: Entrepreneurship is a process of value creation consisting of committing time and effort, considering financial, social and other risks, resulting financial gain. The initial step of entrepreneurship is to recognize opportunities, which refers to a mechanism of intention. Empirical studies have provided evidence that entrepreneurial behavior is best predicted by intention. Intention, in turn, is associated with certain personality traits and attributes. This study aims to investigate the mediating effect of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 55 publications
2
32
0
1
Order By: Relevance
“…Moreover, Kirzner (1997) articulated that alertness refers to the entrepreneurs' cognitive abilities and skills that direct the process of opportunity identification in the market. Gozukara and Colakoglu (2016) explained that entrepreneurial alertness is a state of mind that is open to exploring opportunities at all times, even in uncertain environments with limited resources. Tang et al (2012) suggested that the ability to make the relation between dots by linking them on different occasions is a dynamic feature of recognizing opportunities.…”
Section: Entrepreneurial Passion and Entrepreneurial Alertnessmentioning
confidence: 99%
“…Moreover, Kirzner (1997) articulated that alertness refers to the entrepreneurs' cognitive abilities and skills that direct the process of opportunity identification in the market. Gozukara and Colakoglu (2016) explained that entrepreneurial alertness is a state of mind that is open to exploring opportunities at all times, even in uncertain environments with limited resources. Tang et al (2012) suggested that the ability to make the relation between dots by linking them on different occasions is a dynamic feature of recognizing opportunities.…”
Section: Entrepreneurial Passion and Entrepreneurial Alertnessmentioning
confidence: 99%
“…Entrepreneurs with high innovativeness mainly aimed at profit and development because entrepreneurs have the desire to seek innovative resources, environmental changes and the signs suggestive of opportunities for innovation (Gozukara & Colakoglu, 2016).…”
Section: Innovativenessmentioning
confidence: 99%
“…It includes the development and enhancement of products and services and new administrative techniques and technologies for performing organizational functions (Okhomina, 2010). Schumpeter (1990) explains innovation as a significant entrepreneurial precursor and entrepreneur as an innovator (Gozukara & Colakoglu, 2016), while Covin and Miles (1999) argue that without innovativeness, entrepreneurship cannot exist and that innovativeness is a crucial part of entrepreneurship survival strategies (Omisakin et al, 2016).…”
Section: Innovativenessmentioning
confidence: 99%
See 2 more Smart Citations